2015
DOI: 10.1021/ic502298j
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Dioxide Activation: A Theoretical Investigation into Dual S═O Bond Cleavage by Three-Coordinate Molybdenum(III) Complexes

Abstract: Cummins et al. have observed that 3 equiv of Mo(N[R]Ar)3 (R = C(CD3)2CH3, Ar = 3,5-C6H3Me2) are required for dual S═O bond cleavage within a SO2 molecule. Using density functional theory calculations, this theoretical study investigates a mechanism for this SO2 cleavage reaction that is mediated by MoL3, where L = NH2 or N[(t)Bu]Ph. Our results indicate that an electron transfers into the SO2 ligand, which leads to Mo oxidation and initiates SO2 coordination along the quartet surface. The antiferromagnetic (AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The N-Ru-N bond angles (80.22°-81.48°) are also deviating from (90°). A comparison of the calculated Ru-Cl and Ru-N bond lengths with those of reported Ru(II) complexes involving bidentate N-donor ligands reveals that the average values found for Ru-Cl (2.493 Å) is consistent with the range of the reported values {2.473 (p-cymene)Ru(curcuminato)chloro} [49]. [53].The calculation of atomic charges explains the potential donor and acceptor property of atoms [54].…”
Section: Theoretical Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…The N-Ru-N bond angles (80.22°-81.48°) are also deviating from (90°). A comparison of the calculated Ru-Cl and Ru-N bond lengths with those of reported Ru(II) complexes involving bidentate N-donor ligands reveals that the average values found for Ru-Cl (2.493 Å) is consistent with the range of the reported values {2.473 (p-cymene)Ru(curcuminato)chloro} [49]. [53].The calculation of atomic charges explains the potential donor and acceptor property of atoms [54].…”
Section: Theoretical Studiessupporting
confidence: 75%
“…The energy minimization studies were carried out using the GAUSSIAN 09W software program. Molecular geometries of the singlet ground state of the complexes were fully optimized in the gas phase at the B3LYP/LanL2DZ basis set [48,49]. The optimized geometries of complexes 1-4 are given in Fig.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…The optimized structures were carried out by using the B3LYP/6-31G(d, p) for the ligands and LanL2DZ for the dioxidovanadium (V) complexes basis set; respectively [27,28]. The complexes structure with natural bond order (NBO) charges of atoms are given in Fig.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…In this vein, Armentrout et al., using guided ion beam mass spectrometry, [12] have reported that the activation of the S−O bond of sulfur dioxide by the cations of the heavy transition metals rhenium, [13] osmium, [14] and iridium [15] can only be achieved under endothermic conditions. Naturally, for most of the considerations in this undertaking, the S−O bond activation represents the key issue [16] . Consequently, a better understanding of the SO 2 activation and S−O bond cleavage by transition metals is vital in order to make progress in this field.…”
Section: Introductionmentioning
confidence: 99%